2019
DOI: 10.1029/2018jd029330
|View full text |Cite
|
Sign up to set email alerts
|

A Practical Single‐Channel Algorithm for Land Surface Temperature Retrieval: Application to Landsat Series Data

Abstract: The single‐channel (SC) algorithm has been widely used to retrieve land surface temperature from Landsat series data for its simplicity and requirement of only one thermal infrared channel. The main error sources of the existing SC algorithms are the linearization of the Planck's function and atmospheric correction. This paper proposed a practical SC (PSC) algorithm to retrieve land surface temperature from Landsat series data aiming at avoiding the aforementioned error sources. The sensitivity of the PSC algo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 41 publications
2
42
0
Order By: Relevance
“…In addition to the previous study, Zhang et al [53] also investigated the accuracy of SCA using Landsat 8 imagery and SURFRAD measurements using 40 Landsat 8 scenes acquired in different seasons and different years, and they obtained 1.96 K RMSE. Wang et al [54] reported that Practical Single-Channel Algorithm (PSCA) and generalized SCA provided 1.77 K and 2.24 K RMSE, respectively, in line with our SCA results based on Landsat 8 and Sobrino et al's LSE model. Sekertekin [59] The limitations of this study and future investigations can be reported as follows: (1) Thermal bands have a native spatial resolution of 120 m, 60 m and 100 m for Landsat 5 TM, 7 ETM+, and 8 TIRS, respectively, but they are delivered by USGS at 30-m after cubic convolution resampling.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In addition to the previous study, Zhang et al [53] also investigated the accuracy of SCA using Landsat 8 imagery and SURFRAD measurements using 40 Landsat 8 scenes acquired in different seasons and different years, and they obtained 1.96 K RMSE. Wang et al [54] reported that Practical Single-Channel Algorithm (PSCA) and generalized SCA provided 1.77 K and 2.24 K RMSE, respectively, in line with our SCA results based on Landsat 8 and Sobrino et al's LSE model. Sekertekin [59] The limitations of this study and future investigations can be reported as follows: (1) Thermal bands have a native spatial resolution of 120 m, 60 m and 100 m for Landsat 5 TM, 7 ETM+, and 8 TIRS, respectively, but they are delivered by USGS at 30-m after cubic convolution resampling.…”
Section: Discussionsupporting
confidence: 88%
“…The cross-validation method considers a well-validated LST product as a reference and compares the satellite-derived LST with the referenced (well-validated) LST derived from other satellites [7]. The T-based method, used by many researchers and also considered in this study, directly compares the satellite-based LST with ground-based LST measurements at the satellite overpass [46,[48][49][50][51][52][53][54][55]. The main advantage of the T-based method is that it enables evaluating the radiometric quality of the satellite sensor and the performance of LST retrieval methods depending on atmospheric and emissivity parameters.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As seen in Figures 4 and 5, the model bias of atmospheric downwelling radiances was significant for both VIIRS I4 and I5 bands, while that of the atmospheric transmittance values was relatively insignificant. The atmospheric transmittance could be directly calculated from optical thickness values with the proposed regression model in Equation (11). On the other hand, only path radiance and extinction were considered in the calculation of atmospheric radiances.…”
Section: Corrections Of Model Biasesmentioning
confidence: 99%
“…Conventional single-channel atmospheric correction methods are based on radiative transfer codes or regression models; those require ancillary atmospheric data such as atmospheric profiles, total column precipitable water vapor contents (TPW), and near-surface air temperature [2,4,[11][12][13]. Some recent studies used numerical weather prediction (NWP) models as input atmospheric information for single-channel atmospheric corrections [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%